Protozoa stimulate the plant beneficial activity of rhizospheric pseudomonads - Weidner, Simone (2017)
Aims: The functioning of plant-associated bacteria is strongly influenced by their interaction with other organisms. For instance, bacteria upregulate the production of secondary metabolites in presence of protozoa and we hypothesised that this interaction may contribute to plant health. Methods: Here, we tested if the effect of beneficial pseudomonads on wheat growth and health is modified by co-inoculation with the bacterivorous amoeba Acanthamoeba castellanii. We assessed effects of this co-inoculation in absence and presence of the root pathogen Pythium ultimum. Results: In absence of amoebae, bacterial isolates had few beneficial effects and some isolates exacerbated growth inhibition by the pathogen (despite their reported beneficial effects in vitro). Effects on plant growth in absence and presence of the pathogen were negatively correlated. Co-inoculation with amoebae suppressed this relationship, leading to plant growth promotion in absence and reduction of deleterious effects in presence of the pathogen. The positive effect of amoebae in absence of the pathogen could be related to bacterial siderophore production in vitro. Conclusions: Our results illustrate the discrepancy between in vitro and in vivo effects of plant beneficial bacteria. Incorporation of other rhizospheric trophic components such as protists may be a key factor to influence the plant-beneficial potential of bacteria in vivo.